Gas-liquid hydrodynamics of a fractal flow mixer - Priyambodo, Muhammad; Bhatelia, Tejas; Shah, Milin; Patel, J.; Mazur, M.; Pareek, Vishnu (2023)
Gas-liquid hydrodynamics of a micro-structured device (fractal flow mixer) was experimentally investigated. Experiments were conducted for a range of liquid-to-gas superficial velocity ratios (VSL/VSG). High-speed imaging was used to identify the flow regimes inside the microchannels of the device at different VSL/VSG. At different VSL/VSG, two or more flow regimes were observed simultaneously in different micro-channels. Consequently, a new flow regime map was developed. An optical probe was used to measure the bubble mean size and velocity. The effect of the VSL/VSG towards the bubble mean size, mean velocity, and frequency were analyzed. The bubble mean size decreases with the increase of the VSL/VSG, which can be attributed to the uniform shearing of gas slugs across all channels. To check the consistency of the fractal flow mixer in producing gas bubbles over a single experiment run, the global relative standard deviation (RSD) was used. The fractal flow mixer was able to generate equal flow distribution across the 16 outlets and maintain a Taylor flow over a range of VSL/VSG. However, depending on the VSL/VSG, the GB and GS vary to a certain extent, governed by the capillary effect and the back-pressure.